Human Mesenchymal Stem Cell Morphology and Migration on Microtextured Titanium - Banik, Brittany L.; Riley, Thomas R.; Platt, Christina J.; Brown, Justin L. (Frontiers in Bioengineering and Biotechnology, 2016)
The implant used in spinal fusion procedures is an essential component to achieving successful arthrodesis. At the cellular level, the implant impacts healing and fusion through a series of steps: first, mesenchymal stem cells (MSCs) need to adhere and proliferate to cover the implant; second, the MSCs must differentiate into osteoblasts; third, the osteoid matrix produced by the osteoblasts needs to generate new bone tissue, thoroughly integrating the implant with the vertebrate above and below. Previous research has demonstrated that micro-textured titanium is advantageous over smooth titanium and PEEK implants for both promoting osteogenic differentiation and integrating with host bone tissue; however, no investigation to date has examined the early morphology and migration of MSCs on these surfaces. This study details cell spreading and morphology changes over 24 hours, rate and directionality of migration 6 to 18 hours post seeding, differentiation markers at 10 days, and the long term morphology of MSCs at 7 days, on micro-textured, acid-etched titanium (Endoskeleton), smooth titanium, and smooth PEEK surfaces. The results demonstrate in all metrics, the two titanium surfaces outperformed the PEEK surface. Furthermore, the rough acid-etched titanium surface presented the most favorable overall results, demonstrating the random migration needed to efficiently cover a surface in addition to morphologies consistent with osteoblasts and preosteoblasts.